Использование населением северной части Буковины «даров» животного мира в VIII–XIII вв. - Возний, Ігор; Возний, Ігор (My University, 2021)
I. P. Vozny Use of the “Gifts” of the Animal World by the Population of the Northern Part of Bukovina in the 8th—13th Centuries The article examines the ways of development and specialization of animal husbandry in a particular region, namely the northern part of Bukovina, over a fairly long period from the formation of East Slavic tribal reigns to the Ancient Rus state and the Mongol-Tatar invasion. The development of animal husbandry, the species composition of the herd of domestic animals, depending on the influence of the physical-geographical, natural-climatic and socio-economic conditions of the region is analyzed based on osteoarchaeological material. Such material from the settlements of the study area makes it possible to state the presence of several types of economic specialization of animal husbandry and conclude their quantitative ratio in the study area. So in the Middle Dniester, pig breeding prevailed, followed by sheep breeding and raising cattle (the first type of animal husbandry). On the left bank of the Prut River, with its turf-podzolic loams, preference was given to the breeding of big cattle — small ruminants — pigs (the second species). The third species is presented in the following sequence: cattle — pig breeding — sheep breeding. Hunting products played an important role in the diet of the local population. The species composition of wild game animals, hunting methods, and tools used in this process are analyzed. The study showed a fairly high level of development of animal husbandry and hunting among the local population.
Keywords: animal husbandry; hunting; natural and climatic conditions; osteological material; cattle; small ruminants; wild animals; northern part of Bukovina; fodder base; economic specialization of animal husbandry